Frederick Kiesler : lost in history : Art of This Century and the modern art gallery - Haines-Cooke, Shirley (Cambridge Scholars Pub., 2009)
The material for this book has been taken from the 2006 thesis, Frederick Kiesler's Art of This Century in New York, (1942-1947), in the Context of the Twentieth Century Art Museum. The prime objective was to establish why so few people remember Art of This Century, which Kiesler designed for Peggy Guggenheim in 1942, and she ruthlessly closed in 1947. A second aim was to investigate why there has been so research carried out on the Gallery, when it was acknowledged as a work of art in it ...